CO2 Methanation via Amino Alcohol Relay Molecules Employing a Ruthenium Nanoparticle/Metal Organic Framework Catalyst. Issue 38 (10th July 2020) - Cui, Xinjiang; Shyshkanov, Serhii; Nguyen, Tu N.; Chidambaram, Arunraj; Fei, Zhaofu; Stylianou, Kyriakos C.; Dyson, Paul J.
Abstract: Methanation of carbon dioxide (CO2 ) is attractive within the context of a renewable energy refinery. Herein, we report an indirect methanation method that harnesses amino alcohols as relay molecules in combination with a catalyst comprising ruthenium nanoparticles (NPs) immobilized on a Lewis acidic and robust metal–organic framework (MOF). The Ru NPs are well dispersed on the surface of the MOF crystals and have a narrow size distribution. The catalyst efficiently transforms amino alcohols to oxazolidinones (upon reaction with CO2 ) and then to methane (upon reaction with hydrogen), simultaneously regenerating the amino alcohol relay molecule. This protocol provides a sustainable, indirect way for CO2 methanation as the process can be repeated multiple times. Abstract : Well‐dispersed Ru nanoparticles with narrow size distribution form on a metal–organic framework to afford a catalyst that displays excellent performance in the indirect and sustainable methanation of CO2 using amino alcohols as effective relay molecules.